Importance of risk based internal auditing on growth and sustainability of microfinance institutions: a case of FMC Finance (pvt) Ltd. - Mataruse, Esnath (Midlands State University, 2020)
The general objective of this study was to establish the importance of Risk Based Internal Audit on the growth and sustainability of microfinance institutions. Literature from different authors was reviewed concerning objectives of the research project. Descriptive research design was used in this research, together with case study design and FMC Finance, Harare was used as a case study. The researcher used judgemental sampling to determine the population and sample size. The research used primary data which was collected using self-administered questionnaires and self-conducted interviews. Both qualitative and quantitative approaches were used to collect data. Data collected from questionnaires was analysed and presented using tables, pie charts and graphs. The researcher found out that FMC Finance is a risk naïve company hence traditional auditing approaches are no longer adequate therefore implementing RBIA will enable its sustainability. To note is the difference between TAA and RBIA whereby RBIA saves time and resources through channelling more audit resources towards risky areas than financial statements areas and compliance. The researcher recommended the adoption of RBIA since it is a proactive action which enables the detection of risks and ways of mitigating them are established to avoid future losses which humpers growth of FMC Finance.